PENGEMBANGAN MEDIA BIG BOOK DUA DIMENSI MATERI PERPINDAHAN KALOR/PANAS PADA MATA PELAJARAN IPA KELAS V SEKOLAH DASAR - Rafika Duri; Hetilaniar; Aldora Pratama (STKIP Subang, 2023)
This research was motivated by the emergence of problems at SD Negeri 57 Palembang, namely the absence of interesting and varied learning media in the use of learning media in the learning process, so that students were less interested in participating in learning which caused students to find it difficult to understand the material presented by educators. The purpose of the research is to develop two-dimensional digital big book learning media in order to determine the validity and practicality of the developed big book media. The type of research used is Research and Development (R&D) with the ADDIE model which consists of 5 stages, namely the Analysis stage, the Design Stage, the Development Stage, the Implementation Stage and the Evaluation Stage. The results of the big book learning media research were declared valid, shown in the average percentage results with validation results by material expert validation, namely 87.14% in the